S-3'-hydroxy-7', 2', 4'-trimethoxyisoxane, a novel ferroptosis inducer, promotes NSCLC cell death through inhibiting Nrf2/HO-1 signaling pathway - Jing Chen; Songlin Zhou; Xian Zhang; Huange Zhao (Frontiers Media S.A., 2022)
Background: Ferroptosis is a newly discovered and promising non-apoptotic programmed cell death (PCD), and inducing ferroptosis in cancer cells could open up a novel avenue for drug screening and cancer therapy. S-3'-hydroxy-7', 2', 4'-trimethoxyisoxane (ShtIX), a new isoflavane compound, has been reported to possess cytotoxicity in non-small cell lung cancer (NSCLC). The aim of this research is to explore the ShtIX-induced cell death form and its underlying molecular mechanism in NSCLC cells.Methods: Cell proliferation, cell cycle arrest, and cell death tests were used to assess the ability of ShtIX to kill NSCLC cells. Iron metabolism, Fe2+ content, reactive oxygen species (ROS) production, lipid peroxide (MDA) level, glutathione (GSH) level, and glutathione peroxidase 4 (GPX4) level were used to determine ferroptosis caused by ShtIX. We employed western blot, quantitative real-time PCR, and Nrf2 interference in NSCLC cells to investigate the roles of Nrf2/HO-1 in ShtIX-induced ferroptosis. In a xenograft nude mouse model, the anticancer efficacy of ShtIX and the function of ferroptosis were studied.Results: Our research shows that ShtIX can selectively kill NSCLC cells while sparing normal cells and that ShtIX-induced cell death can be efficiently reversed by the ferroptosis inhibitors and the iron chelator, but not by other cell death inhibitors. After cells were treated with ShtIX, there was an increase in Fe2+ content and lipid peroxidation accumulation, as well as a drop in GSH and GPX4 levels, all of which are indicators of ferroptosis. ShtIX also reduced the expression of Nrf2 and HO-1, and genetic Nrf2 silencing in NSCLC enhanced the effect of ShtIX-induced ferroptosis. Additionally, ShtIX retards tumor growth and induced ferroptosis through Nrf2/HO-1 signal pathway in the A549 xenograft model, whereas Fer-1 lessens the anticancer effect.Conclusion: This work provided the evidence that ShtIX caused ferroptosis in NSCLC cells, and inhibiting the Nrf2/HO-1 pathway can considerably exacerbate the effect of ShtIX-induced ferroptosis. The study establishes ShtIX as a promising natural ferroptosis inducer for the treatment of NSCLC.